Age difference between parents influences parity and number of sons. Issue 3 (19th January 2018) - Kuna, Berenika; Galbarczyk, Andrzej; Klimek, Magdalena; Nenko, Ilona; Jasienska, Grazyna
Abstract: Objectives: Among couples, women usually prefer slightly older men, and men tend to choose much younger partners. Age difference between partners has been shown to influence their parity; however, results of previous studies are inconsistent. This study analyzed relationships between husband and wife age difference and their total number of children, and number of daughters and sons in a contemporary, rural Polish population. Methods: Demographic and reproductive data were collected from 384 postmenopausal women from rural Poland who were married only once. Regression models were used to evaluate the impact of the age gap between partners on total number of children and on number of daughters and sons. Women's age, age at marriage (as an indicator of reproductive value), and years of education were used in analyzes as potential confounders. Results: There was an inverted U‐shape association between parental age difference and number of children and also the number of sons. The highest number of children and sons was observed when men were approximately 6.5 years older than their wives. There was no significant relationship between parental age difference and number of daughters. Conclusions: Age difference between partners is important for reproductive success (with younger wives having higher reproductive potential) and is also related to number of sons. Older husbands might provide more resources for the family, thus facilitating production of well‐nourished male offspring. Future research should evaluate not only number of children but also their biological condition, health, and lifetime achievements in relation to the age difference between their parents.